Peran Pendidikan Matematika dalam Membangun Keterampilan Literasi Numerik di Sekolah Dasar - Hardika Saputra (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2026)
This study aims to examine the role of mathematics education in building numerical literacy in elementary schools, as well as strategies that can be implemented to enhance students' numerical skills. Numerical literacy is a fundamental skill needed by students to understand, interpret, and use numerical information in daily life. The research method used is library research, reviewing various related literature, including books and recent scholarly journals in the field of mathematics education. The results show that the integration of technology, the use of contextual approaches, and collaborative learning are effective strategies in improving students' numerical literacy. Technology helps simplify the understanding of abstract concepts, while contextual and collaborative approaches make mathematics more relevant and applicable. The implications of these findings are the need for further development in teacher training to integrate technology in teaching and the importance of involving students in more interactive and contextual learning processes. This study also suggests further evaluation of the implementation of these strategies in various educational settings.